What is the Evaluating the Roles of Lifestyle, Genetics, and Menstrual Cycle in Polycystic Ovarian Syndrome: A Meta-Analysis - Pramukawati, Dian Ayu; Ayu Rachmawati, Rulita; Levi Rismawati, Normalia; Murti, Bhisma; Mar'atul Munawaroh , Siti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: The WHO in 2023 reports that polycystic ovary syndrome (PCOS) has affected about 8–13% of women of reproductive age. Some studies report that lifestyle, hormones, and genetics are one of the risk factors for PCOS. This study aims to analyze and estimate the magnitude of the effects of obesity, smoking, irregular menstruation, and having a family history of PCOS with the incidence of PCOS in women of childbearing age. Subjects and Method: Systematic review and meta-analysis studies were conducted according to the PRISMA flowchart and PICO model. Population: women of childbearing age. Intervention: obesity, smoking, irregular periods, and a family history of PCOS. Comparison: Normal BMI, no smoking, regular periods, and no family history of PCOS. Outcome: PCOS. The basic data used involves Google Scholar, PubMed, BMC, ScienceDirect, and Springer Link. The inclusion criteria are full-text articles with observational study design using multivariate analysis that attaches aOR values and is published from 2013-2024. Data analysis using Review Manager 5.3 application. Results: Five primary studies were used to analyze obesity with PCOS. Women with obesity had 2.49 times the risk of developing PCOS compared to non-obese (OR= 2.49; CI 95%= 1.59 to 3.88; p < 0.001). Five primary studies were used to analyze smoking with PCOS. Women with smoking habits have a risk of developing PCOS 1.42 times compared to nonsmokers (OR= 1.42; CI 95%= 1.04 to 1.95; p= 0.03). Ten primary studies were used to analyze irregular periods with PCOS. Women with irregular periods had a 3.32 times risk of developing PCOS compared to regular periods (OR= 3.32; CI 95%= 2.77 to 3.97; p < 0.001). Eleven primary studies used for analysis had a family history of PCOS with PCOS. Women with a family history of PCOS had a 2.94 times higher risk of having PCOS than no family history of PCOS (OR= 2.94; CI 95%= 2.11 to 4.09; p < 0.001). Conclusion: Obesity, smoking, irregular periods, and a family history of PCOS increase the risk of PCOS in women of childbearing age.